Agents’ factors that predict customer-orientation behaviour at Ikhlas Consultant and Services (ICS), Bukit Katil, Melaka / Nurul Naim Mohd Yusof - Mohd Yusof, Nurul Naim (2011)
Agents are employees who act as a representative of the company. However, none of us know the behaviour of agents when they come to approach us or run the product toward the customers. For them, to approach customers is a challenging to them as they need to have high self confident level and the physical and mental support from various factors. Most important factors is self motivation inside themselves while another support is from the commitment of employers or company towards them. This research was conducted for the purposed to know the behaviour of agents’ prediction on customer-orientation at Ikhlas Consultant and Services (ICS), Bukit Katil Melaka. The main objective of this research was to identify the individual factors of agents’ behaviour towards customers by study the factors of organizational commitment, self-monitoring and intrinsic motivation of agents. The respondent of this study was the agents whose work at the Ikhlas Consultant & Services (ICS). From the questionnaires distributed and the feedback gathered from 50 takaful agents were used to test the hypothesized relationship as well as the frequency of the commitment to the organization. From the findings, the academic and managerial implication of this study is discussed and has been provided with conclusion and recommendation.